Views and practices of mathematical method for physics lecture at pre-service physics teachers. Issue 1 (March 2021) - Sujito,; Pratiwi, H Y; Soewono, E; Suhandi, A; Liliasari, S
Abstract: The aim of study is to investigate the lecture process of Mathematical Method for Physics. The model is to develop the concept and ability of mathematical logical thinking of students of Physics Education Study Program. Mathematical Method for Physics is used to study physics related to how to systematically find out about nature. The research subjects consisted of 2 lecturers, and students who had taken Mathematical Method for Physics Courses, namely levels 3 and 4. The number of students filling out questionnaires was 94 students. Observations were conducted in class. Observations are focused on the learning process in the class. Data was collected using questionnaires to get student responses to the implementation of lectures. The results of the study were as many as 57.82% of students gave positive statements about the implementation of lectures, while the rest gave negative statements. This shows that studying physics is not only mastery of a collection of knowledge in the form of facts, concepts, or principles, but also an inquiry process. Therefore, the challenge in facing the 21st century is to improve the quality of education. Learning innovation is adjusted to the demands of educational change in the era of industrial revolution 4.0 (millennial). Learning must utilize information, communication, and technology (ICT). Innovation requires the support of a learning process that can strengthen creativity through critical thinking skills.